Logic of experimentation : reshaping music performance in and through artistic research - Assis, Paulo de (Orpheus Institute series., 2018)
Beyond interpretation: a proposal for experimental performance practices.0'Logic of Experimentation' offers several innovative and ground-breaking perspectives on music performance, music ontology, research methodologies and ethics of performance. It proposes new modes of thinking and exposing past musical works to contemporary audiences, arguing for a new kind of performer, emancipated from authoritative texts and traditions, whose creativity is propelled by intensive research and inventive imagination. Moving beyond the work-concept, Logic of Experimentation presents a new image of musical works, based upon the notions of strata, assemblage and diagram, advancing innovative practice-based methodologies that integrate archival and musicological research into the creative process leading to a performance. Beyond representational modes of performance - be it mainstream or historically informed performance practices - 'Logic of Experimentation' creates an ontological, methodological and ethical space for experimental performance practices, arguing for a new mode of performance. Written in an experimental style, its eight chapters appropriate music performance concepts from post-structural philosophy, psychoanalysis, science and technology studies, epistemology and semiotics, displaying how transdisciplinarity is central to artistic research.